The INtegrated CAtchment model of phosphorus dynamics (INCA-P): Description and demonstration of new model structure and equations. (September 2016) - Jackson-Blake, L.A.; Wade, A.J.; Futter, M.N.; Butterfield, D.; Couture, R.-M.; Cox, B.A.; Crossman, J.; Ekholm, P.; Halliday, S.J.; Jin, L.; Lawrence, D.S.L.; Lepistö, A.; et al.
Abstract: INCA-P is a dynamic, catchment-scale phosphorus model which has been widely applied during the last decade. Since its original release in 2002, the model structure and equations have been significantly altered during several development phases. Here, we provide the first full model description since 2002 and then test the latest version of the model (v1.4.4) in a small rural catchment in northeast Scotland. The particulate phosphorus simulation was much improved compared to previous model versions, whilst the latest sorption equations allowed us to explore the potential time lags between reductions in terrestrial inputs and improvements in surface water quality, an issue of key policy relevance. The model is particularly suitable for use as a research tool, but should only be used to inform policy and land management in data-rich areas, where parameters and processes can be well-constrained. More long-term data is needed to parameterise dynamic models and test their predictions. Highlights: We describe the latest version of INCA-P, a dynamic catchment phosphorus model. This is the first full description of the model structure and equations since 2002. A test application demonstrates improved model performance. New sorption equations allow the impacts of legacy soil P to be simulated over time. Model applicability and limitations are discussed.